Morning Glory Disc Anomaly Associated with Ipsilateral Optic Nerve and Chiasm Thickening: Three Cases and Review of the Literature - Doneda, Chiara; Pinelli, Lorenzo; Scaramuzzi, Matteo; Galli, Jessica; Fazzi, Elisa; Parazzini, Cecilia; Righini, Andrea; Nucci, Paolo (Neuropediatrics, 2017)
Several extraorbital findings have been described in morning glory disc anomaly (MGDA), including optic pathway abnormalities. We want to emphasize the importance of looking for ipsilateral optic nerve and chiasm thickening in MGDA-affected patients because we think that it may be a relevant common associated finding to date not stressed by anyone. We report three cases of clinically diagnosed unilateral MGDA in which magnetic resonance imaging revealed enlargement of the ipsilateral optic nerve and chiasm. A literature analysis was made and previously reported MGDA cases, and case series were checked, looking for described, or misunderstood similar magnetic resonance imaging findings. Three other cases with very similar prechiasmatic optic nerve and chiasm findings were identified from the literature. Two further cases are discussed as possibly characterized by similar misinterpreted magnetic resonance features. Our study broadens the constellation of intra- and extraorbital findings of MGDA. Though magnetic resonance imaging is not sufficient to determine the neuropathological substrate of this finding, clinicians and radiologists should be aware of the possible association of MGDA with ipsilateral thickening of the optic nerve and chiasm, to properly plan the clinical and imaging follow-up.
Keywords: morning glory disc anomaly; optic nerve; MRI